Orbital competition of Mn3+ and V3+ ions in Mn1+xV2-xO4. (29th January 2021) - Jiao, J L; Zhang, H P; Huang, Q; Wang, W; Sinclair, R; Wang, G; Ren, Q; Lin, G T; Huq, A; Zhou, H D; Li, M Z; Ma, J
Abstract: The structural and magnetic properties of Mn1+ x V2- x O4 (0 < x ⩽ 1) have been investigated by the heat capacity, magnetization, x-ray diffraction and neutron diffraction measurements, and a phase diagram of temperature versus composition was built up. For x ⩽ 0.3, a cubic-to-tetragonal ( c > a ) phase transition was observed. For x > 0.3, the system maintained the tetragonal lattice. Although the collinear and noncollinear magnetic transitions of V 3+ ions were obtained in all compositions, the canting angles between the V 3+ ions decreased with Mn 3+ -doping, and the ordering of the Mn 3+ ions was only observed as x > 0.4. In order to study the dynamics of the ground state, the first principles simulation was applied to analyze not only the orbital effects of Mn 2+, Mn 3+, and V 3+ ions, but also the related exchange energies.